PENERAPAN MODEL BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PGSD FKIP UNIVERSITAS QUALITY MEDAN - Widiyarti, Gemala; Anggraini, Lisa; Aritonang, Nur H Sa’diyah (JURNAL CURERE, 2023)
This type of research is classroom action research which consists of two cycles, each cycle being held in 4 meetings. Research procedures include planning, implementation of action, observation, and reflection. The subjects in this study were PGSD students at Quality University. The results showed that in the first cycle, 37% completed the individual criteria for critical thinking skills or were in the less critical category, classically they had not been fulfilled because the average score was 60. Meanwhile, in the second cycle, 88% of students completed has met the criteria for critical thinking ability and classically has been fulfilled, namely the average value obtained is 85 or is in the very critical category. Based on the results of the research above, it can be concluded that the critical thinking skills of PGSD students through the guided Problem Based Learning (PBL) learning model have increased.